2003
DOI: 10.1021/bi034195+
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Interfacial Binding of Bacterial Phosphatidylinositol-Specific Phospholipase C

Abstract: The interactions of PI-PLC with nonsubstrate zwitterionic [phosphatidylcholine (PC)] and anionic [phosphatidylmethanol (PMe), phosphatidylserine, phosphatidylglycerol, and phosphatidic acid] interfaces that affect the catalytic activity of PI-PLC have been examined. PI-PLC binding is strongly coupled to vesicle curvature and is tighter at acidic pH for all of the phospholipids examined. PI-PLC binds to small unilamellar vesicles (SUVs) of anionic lipids with much higher affinity (K(d) is 0.01-0.07 microM for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(89 citation statements)
references
References 28 publications
8
80
0
1
Order By: Relevance
“…Tyr 57 , a surface residue that is not situated at the putative dimer or membrane interface, was included as a control. As shown in Table 1, all Cys mutants but W242C exhibited nK d values (for POPC small unilamellar vesicles) comparable with the 64 Ϯ 3 M previously obtained for recombinant PI-PLC (29). Previous work showed that W242A lost significant affinity for PC with an apparent dissociation constant of 8600 Ϯ 600 M (20).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Tyr 57 , a surface residue that is not situated at the putative dimer or membrane interface, was included as a control. As shown in Table 1, all Cys mutants but W242C exhibited nK d values (for POPC small unilamellar vesicles) comparable with the 64 Ϯ 3 M previously obtained for recombinant PI-PLC (29). Previous work showed that W242A lost significant affinity for PC with an apparent dissociation constant of 8600 Ϯ 600 M (20).…”
Section: Resultssupporting
confidence: 77%
“…Removal of these two tryptophan residues, singly or together, dramatically increases the apparent K D (or nK d in a Langmuir adsorption model for binding (29)) for partitioning of the enzyme onto PC vesicles, and the magnitude of the change is consistent with the change in free energy for removing a group that partitions into the PC membrane. X-ray crystallography was used to investigate protein structural changes that might be associated with the W47A/W242A mutation and to determine whether such changes might occur in the active site, resulting in a lower k cat .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…SUVs of the anionic phospholipid dioleoylphosphatidylglycerol (used as the substrate analog) with different mole fractions of 1-palmitoyl-2-oleoyl-PC were prepared by sonication. FCS data were analyzed as previously described (23,26 (27) to separate vesicle bound and free protein, with quantification of free protein with the Bio-Rad DC protein assay, was used to compare the fraction of other related protein variants bound to 1 mM PG/PC (1:4) in 50 mM MES, pH 6.5, with 140 mM salt added.…”
mentioning
confidence: 99%
“…Yet such knowledge is likely to be very useful in understanding how proteins and assemblies interact with this interfacial region. For example, there is indirect evidence that the peripheral membrane protein phosphatidylinositol-specific phospholipase inserts a tryptophan residue into a phosphatidylcholine membrane surface, which in turn activates the enzyme toward its substrates, but how this happens in detail is unknown (3,4).…”
mentioning
confidence: 99%